Identifying Sources of Business Cycle Fluctuations in Germany 1975–1998 - Oliver Holtemöller; Torsten Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
In this paper, we estimate a small New Keynesian dynamic stochastic general equilibrium (DSGE) model for Germany for the period from 1975 to 1998 and use it to identify the structural shocks, which have driven the business cycle. For this purpose we apply indirect inference methods, that is we specify the parameters of the theoretical model such that simulated data mimics observed data as closely as possible. In addition to the identification of structural shocks, we uncover the unobservable output gap, which is a prominent indicator in business cycle analysis. Furthermore, we show to which extent each identified shock has contributed to the business cycle fluctuations. - Business cycle accounting ; dynamic stochastic general equilibrium models ; Germany ; indirect inference ; New Keynesian macroeconomics
Keywords: C32; C51; E32; 330; Konjunktur; Dynamisches Gleichgewicht; Ungleichgewichtstheorie; Schock; Schätzung; Deutschland